Cataract: Opacification of the Eye Lens and Its Modern Treatment Methods - Maxamattursunov Omadjon Abdushukir o‘g‘li (Periodica Journal, 2025)
This article thoroughly analyzes the process of lens opacification caused by cataracts, its causes, clinical signs, and modern treatment methods. The pathophysiology of cataracts is explained based on the anatomy of the eye and the functional significance of the lens. Special attention is given to the modern surgical technique of phacoemulsification and the advantages of artificial lens implantation. The article also provides practical recommendations on prevention and rehabilitation. The scientific and practical value of the research lies in early detection of cataracts, effective treatment using advanced technologies, and prevention of complications.
Keywords: cataract; eye lens; visual impairment